Efek Mckenzie Exercise dan Mechanical Lumbar Traction terhadap Perubahan Lingkup Gerak Sendi dan Fungsional Lumbal pada Penderita HNP Lumbal - Tiar Erawan; Sudaryanto Sudaryanto; Andi Nur Hijriyani; Rahmat Nugraha (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Herniated Nucleus Pulposus causes radicular pain due to pressure on the nerve roots resulting in various physical problems, especially limitations in lumbar movement and lumbar function. The aim of this research was to determine the difference in effectiveness between the combination of Interferential Current (IFC), McKenzie exercise and the combination of Interferential Current (IFC), Mechanical Lumbar Traction on changes in Range of Motion (ROM) and lumbar function in Lumbar HNP sufferers. This type of research was a quasi experiment with a pretest–posttest design with control group, using instruments in the form of an inclinometer and the ODI questionnaire. The research was conducted at RSAD Tk. II Pelamonia Makassar. The sample was 14 people suffering from grade 1 and 2 lumbar HNP who were randomly divided into 2 groups, namely the treatment group given IFC and McKenzie, the control group given IFC and Lumbar Mechanical Traction. Data analysis was performed by t test. Based on the paired samples t-test in the control group, the value obtained was p = 0.000 (flexion and lateral lumbar flexion), p = 0.001 (ODI), while in the treatment group the value obtained was p = 0.000 (flexion, lateral lumbar flexion, ODI) which means that IFC and Lumbar Mechanical Traction interventions as well as IFC and McKenzie Exercise can produce significant changes in flexion, lateral flexion and functional ROM of the lumbar region. Then, based on the independent samples t-test, the values obtained were p = 0.348 (lumbar flexion), p = 0.129 (lateral lumbar flexion), p = 0.670 (ODI) which means that there was no significant difference between the combination of IFC, McKenzie Exercise and IFC, Lumbar Mechanical Traction on changes in flexion, lateral flexion and lumbar functional ROM. IFC and McKenzie are no more effective than IFC and Lumbar Mechanical Traction in changing lumbar flexion and lateral flexion ROM and lumbar functional ability in sufferers of lumbar HNP.Keywords: McKenzie exercise; lumbar mechanical traction; lumbar range of motion; lumbar function ABSTRAK Herniated Nucleus Pulposus menyebabkan nyeri radikular akibat penekanan pada akar saraf sehingga timbul berbagai problem fisik, khususnya keterbatasan gerak lumbal dan fungsional lumbal. Tujuan penelitian ini adalah mengetahui perbedaan efektivitas antara kombinasi Interferential Current (IFC), McKenzie exercise dan kombinasi Interferential Current (IFC), Mechanical Lumbar Traction terhadap perubahan Range of Motion (ROM) dan fungsional lumbal pada penderita HNP Lumbal. Jenis penelitian ini adalah quasi experiment dengan desain pretest–posttest with control group, menggunakan instrumen berupa inclinometer dan kuisioner ODI. Penelitian dilaksanakan di RSAD Tk. II Pelamonia Makassar. Sampel adalah penderita HNP lumbal grade 1 dan 2 sebanyak 14 orang yang dibagi secara acak kedalam 2 kelompok yaitu kelompok perlakuan diberikan IFC dan McKenzie, kelompok kontrol diberikan IFC dan Mechanical Traction Lumbal. Analisis data dilakukan dengan uji t. Berdasarkan paired samples t-test pada kelompok kontrol diperoleh nilai p = 0,000 (fleksi dan lateral fleksi lumbal), p = 0,001 (ODI), sedangkan pada kelompok perlakuan diperoleh nilai p = 0,000 (fleksi, lateral fleksi lumbal, ODI) yang berarti bahwa intervensi IFC dan Mechanical Traction Lumbal serta IFC dan McKenzie Exercise dapat menghasilkan perubahan ROM fleksi, lateral fleksi dan fungsional lumbal yang signifikan. Kemudian, berdasarkan independent samples t-test diperoleh nilai p = 0,348 (fleksi lumbal), p = 0,129 (lateral fleksi lumbal), p = 0,670 (ODI) yang berarti bahwa tidak ada perbedaan yang signifikan antara kombinasi IFC, McKenzie Exercise dan IFC, Mechanical Traction Lumbal terhadap perubahan ROM fleksi, lateral fleksi, dan fungsional lumbal. IFC dan McKenzie tidak lebih efektif daripada IFC dan Mechanical Traction Lumbal terhadap perubahan ROM fleksi dan lateral fleksi lumbal serta kemampuan fungsional lumbal pada penderita HNP lumbal.Kata kunci: McKenzie exercise; mechanical traction lumbal; lumbal range of motion; fungsional lumbal